NBT test in children with iron deficiency anemia (NBT test in iron deficiency) - Özgüner, Seyhan; Altay, Çiğdem; Yetgin, Sevgi (The Turkish Journal of Pediatrics, 1975)
The capacity of granulocytes to reduce NBT dye during phagocytosis was studied in 45 children with iron deficiency anemia and in 19 healthy children. No difference was found in dye reduction between the control and study groups.